Analysis of the students’ educational work on the TSATU moodle system - Kryvonos, I. O. (My University, 2021)
One of the most common ways of controlling the gained knowledge and skills is accomplished with the help of open information systems, like the Moodle LMS (Moodle - Modular Object-Oriented Dynamic Learning Environment). LMS (a learning management system), courses, is a virtual learning environment that allows creating a holistic working space for all participants in the educational process.
Keywords: Moodle LMS; educational process; learning; lecture materials; information